Utility of Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) as A Predictor of Mortality in COVİD-19 - Riya Sunil; Preethi Chikkanayakanahalli Ramesh; Ashwini Hosahalli Nagaraj; Krupa Kadarappa (Medical Laboratory Technology Journal, 2022)
Coronavirus-19 pandemic has stricken our world since December 2019; the disease, first reported in China, is now a pandemic. More than 400 million people have been affected, and 5 million people have succumbed to the disease. Hence, it is the need of the era to find readily available laboratory parameters to assess the mortality chances in these patients. Our study aims to determine the utility of NLR and PLR ratios as a predictor of severity and clinical outcome of COVID-19 patients.100 patients admitted to a tertiary care hospital in Karnataka, India, during the months April to July 2020 were studied. Only patients with a positive RT-PCR (Reverse Transcriptase Polymerase Chain Reaction) report for COVID-19 were included. Demographic data, comorbidities, and mortality status were collected from electronic hospital records. Lab parameters including- Total Count (TC), Absolute count of neutrophils and lymphocytes, platelet count were taken. NLR and PLR were derived from available lab parameters. Patients were categorized into varying severity depending on their SpO2 levels at admission. Neutrophil count (P=0.001) and NLR (P=0.002) were associated with an increased risk of mortality and disease severity. An increase in PLR ratio (P=0.05) shows a mild association with mortality but not with disease severity (P=0.096). In contrast, comorbidities, increasing age, and gender did not show any statistical significance for mortality. The presence of statistical significance concerning NLR and PLR should be utilized as an aid by clinicians to assess disease severity and chances of mortality. As new variants of the disease are uprising and a single therapeutic measure is not available currently for the treatment of COVID-19, clinicians should be well informed about how to monitor the disease in a cost-effective and easily accessible way to reduce the disease mortality and morbidity.